Transcriptomic response to salinity variation in native and introduced mud-tidal gastropod Batillaria attramentaria - Patra, Ajit Kumar; Ho, Phuong-Thao; Won, Yong-Jin (Frontiers in Marine Science, 2023)
The introduced Asian mud-tidal gastropod Batillaria attramentaria has been reported to quickly dominate its new habitat, Elkhorn Slough, USA, which has a different osmotic condition from its native habitat. This species has also been reported to have a substantial impact on the ecosystem of the new habitat. In this study, we compared the gene expression profiles in response to temporary salinity variation in native (Asian) and introduced (North American) snails and elucidated the genetic mechanism underlying such rapid adaptation of the introduced species. We examined the transcriptomes of four B. attramentaria populations, including three from the native habitats and one from the introduced habitat, in response to salinity variation. We found that 2,353, 2,505, 10,362, and 16,381 genes were differentially expressed due to their lineages (Kuroshio vs. Tsushima), origins (native vs. introduced), locations (Korea, Japan, or the USA), and salinity variations (stressful: 13, 23, and 43 PSU vs. optimal: 33 PSU), respectively. We found that GO-enriched differentially expressed genes involved in the detection of various abiotic and biotic stimuli through sensory perception and genes involved in response to abiotic stimulus and stress were upregulated when exposed to lower-salinity conditions in all locations. The results indicated that B. attramentaria has adapted well to varied salinity conditions and evolved after around 100 years of invasion in Elkhorn Slough. This study provides valuable transcriptomic data on salinity stress response genes in the tidal gastropod and contributes to the research on the adaptive evolution of coastal gastropods.